Induction and differential expression of certain novel proteins in Anabaena L31 under UV-B radiation stress - Babele, Piyoosh K.; Singh, Garvita; Kumar, Ashok; Tyagi, Madhu B. (Frontiers in Microbiology, 2015)
For examining how UV-B radiation alters the proteome of the N2-fixing cyanobacterium, Anabaena L31, we extracted proteins from cultures irradiated with UV-B + white light and controls (white light irradiated) and analyzed the proteins using two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). Twenty one proteins, including 2 hypothetical proteins were identified and placed in 8 functional categories. However several of the proteins were housekeeping proteins involved in key metabolic processes such as carbon, amino acid biosynthesis and energy metabolism, certain proteins seem to have a role in stress (antioxidative enzymes), translation, cellular processes and reductases. Two novel hypothetical proteins (all3797 and all4050) were characterized in detail. These two were over-expressed after UV-B irradiation and characterized as FAS 1 (all3797) and PRC barrel-like (all4050) proteins. Bioinformatics analysis revealed that the genes of both the hypothetical proteins have promoter regions as well as transcription binding sites in their upstream region (UTR). Promoters present in all3797 genes suggest their crucial role against UV-B and certain other abiotic stresses. To our knowledge these novel proteins have not been previously reported in any Anabaena strains subjected to UV-B stress. Although we have focused our study on a limited number of proteins, results obtained shed light on the highly complicated but poorly studied aspect of UV-B radiation-mediated changes in the proteome and expression of proteins in cyanobacteria.